A REVIEW ON DIFFERENT TECHNIQUES USED IN DESIGN OF ULTRA WIDEBAND SLOT ANTENNA FOR IMPROVEMENT OF VARIOUS PARAMETER - Miss. Vaishali S. Varpe; Prof. Mrs. R P.Labade (International Journal of Innovations in Engineering Research and Technology, 2021)
An Ultra-Wideband patch antenna plays a major role in communications. This article deals with the broad review of Micro strip patch antenna design parameters such as Reflection Coeffient,VSWR,Impedance,Gain,Effiency,Radiation Pattern etc. various slots for different applications i.e. designs, development of output factors etc. In this modern world a dual band and triple band antenna with notch characteristics plays a vital role in wireless communications like UWB, WLAN, WiMAX etc. In this paper we study about the dual band and triple band characteristics and applications. The good impedance bandwidth, efficiency, Radiation pattern, VSWR can be improved by using the different slots, truncating corner of ground Plane ,feeding techniques, resonance frequency, and dielectric substrate.